2010
DOI: 10.1080/09593330903470701
|View full text |Cite
|
Sign up to set email alerts
|

Boron recovery from clay waste using Diaion CRB‐02 resin

Abstract: A two-step process for boron recovery from clay waste is proposed in the present work. The leachate obtained after the clay waste was leached with sulphuric acid solution was treated with Diaion CRB-02 - a boron-specific resin for the separation of boron from the alkaline species in the leachate. The batch studies showed that a maximum boron recovery of about 95% was obtained at a pH value of 8.0, an initial boron concentration of 50 mg L(-1), a contact time of 24 h and a temperature of 25 degrees C. Equilibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…This increase was due to the exothermic nature of adsorption . While a similar temperature effect was obtained for Diaion CR 02 resin , the reverse of the trend obtained in the present study was reported for Amberlite IR‐743 resin . The boron adsorption capacities of Purolite S 108 resin for 1, 15, 30, 45, and 60°C were found as 9.013, 8.272, 7.765, 7.338, and 7.260 mg/g, respectively.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…This increase was due to the exothermic nature of adsorption . While a similar temperature effect was obtained for Diaion CR 02 resin , the reverse of the trend obtained in the present study was reported for Amberlite IR‐743 resin . The boron adsorption capacities of Purolite S 108 resin for 1, 15, 30, 45, and 60°C were found as 9.013, 8.272, 7.765, 7.338, and 7.260 mg/g, respectively.…”
Section: Resultssupporting
confidence: 88%
“…This result was attributed to an increasing molar fraction of monoborate and polyborate anions with initial pH increase to pH 8.5 . A similar pH effect on boron removal was reported for other N ‐glucamine‐type chelating resins such as Amberlite IR‐743 and Diaion CRB 02 . The pH change of solutions with time is given in Fig.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Therefore, the aluminium hydroxide flocs showed highest removal efficiency against boric acid molecule and monoborate anion at pH 8 as related with the equilibrium by OH ions. Because OHanions compete with the boron ions at high pHs above 9 and removal efficiency decreased above pH 9 [17].…”
Section: Ph Effect On Boron Removalmentioning
confidence: 99%
“…For boron removal, the main processes that have been studied are: (1) coagulation and coprecipitation [6][7][8], (2) ion-exchange using boron-selective ion-exchange resins [9][10][11], (3) solvent extraction [12,13], (4) membrane technologies [14][15][16] and (5) adsorption on activated carbon [17][18][19][20]. Among them, the use of boronselective resins is the most efficient method, but in contrast it is not economical because of high regeneration costs and expensive resins [21,22].…”
Section: Introductionmentioning
confidence: 99%